Report of new species of ciliate from the genus Metaradiophrya (Heidenrich, 1935) in Pheretima elongata from Aurangabad district (M.S.) India. - Bhandari, J C; Nikam, S V; Kanse, V S (Journal of Experimental Sciences, 2012)
New species of ciliates belong to genus Metaradiophrya was recorded from intestine of Pheretima elongata, collected from Aurangabad district (M.S.). In the present study, morphological characteristics of this ciliate and its similarities and differences were discussed compared with other species of this genus.